A Bluetooth-Based Architecture for Contact Tracing in Healthcare Facilities - Piergiuseppe Di Marco; Pangun Park; Marco Pratesi; Fortunato Santucci (Journal of Sensor and Actuator Networks, 2020)
With the latest standard releases, Bluetooth technology is becoming more and more relevant for building and industrial automation. At the same time, Bluetooth is now becoming fundamental for contact tracing applications, to support monitoring and containment of the COVID-19 pandemic. Critical facilities such as nursing homes and hospitals have been severely exposed to the pandemic, but the currently available short-range wireless technology still faces the fundamental limits of proximity accuracy, battery lifetime, and privacy in those complex indoor environments. The aim of this paper is to investigate effective ways of building an architecture with heterogeneous devices to support contact tracing in critical scenarios such as healthcare facilities, while meeting the required level of accuracy and privacy. A framework based on standard Bluetooth mesh networking technology is proposed, and the research challenges are discussed.